Diagnostic validity of methods for assessment of swallowing sounds: a systematic review - Taveira,Karinna Veríssimo Meira (2018)
Abstract Introduction: Oropharyngeal dysphagia is a highly prevalent comorbidity in neurological patients and presents a serious health threat, which may lead to outcomes of aspiration pneumonia, ranging from hospitalization to death. This assessment proposes a non-invasive, acoustic-based method to differentiate between individuals with and without signals of penetration and aspiration. Objective: This systematic review evaluated the diagnostic validity of different methods for assessment of swallowing sounds, when compared to videofluroscopy swallowing study to detect oropharyngeal dysphagia. Methods: Articles in which the primary objective was to evaluate the accuracy of swallowing sounds were searched in five electronic databases with no language or time limitations. Accuracy measurements described in the studies were transformed to construct receiver operating characteristic curves and forest plots with the aid of Review Manager v. 5.2 (The Nordic Cochrane Centre, Copenhagen, Denmark). The methodology of the selected studies was evaluated using the Quality Assessment Tool for Diagnostic Accuracy Studies-2. Results: The final electronic search revealed 554 records, however only 3 studies met the inclusion criteria. The accuracy values (area under the curve) were 0.94 for microphone, 0.80 for doppler, and 0.60 for stethoscope. Conclusion: Based on limited evidence and low methodological quality because few studies were included, with a small sample size, from all index testes found for this systematic review, doppler showed excellent diagnostic accuracy for the discrimination of swallowing sounds, whereas microphone-reported good accuracy discrimination of swallowing sounds of dysphagic patients and stethoscope showed best screening test.